Social Comparisons, Self-Conceptions, and Attributions: Assessing the Self-Related Contingencies in Leader-Member Exchange Relationships - Lapointe, Émilie; Vandenberghe, Christian; Ben Ayed, Ahmed K.; Schwarz, Gary; Tremblay, Michel; Chenevert, Denis (Springer, 2019)
Research on leader-member exchange (LMX) has demonstrated that, in addition to the value of LMX as an indicator of quality relationships with leaders, employees also evaluate how their relationship with the leader compares to other employees’ relationship with the leader. This finding led to the emergence of LMX social comparison (LMXSC). This study examines how LMX vs. LMXSC relates to work outcomes and considers the employee and perceived supervisor self-concept levels as moderators. We posit that LMX predicts work performance through increased organizational commitment. We further suggest that the relational and collective levels of the self-concept act as contingencies of the relationships among LMX, LMXSC, commitment, and performance. A sample of 250 employee-supervisor dyads was used to test the hypotheses. LMX predicted commitment and, indirectly, performance. The employee and perceived supervisor relational self-concepts acted as moderators of LMXSC, and the perceived supervisor collective self-concept acted as a moderator of LMX and LMXSC. However, not all moderation hypotheses were supported. Unexpected moderating effects involving the employee and perceived supervisor individual self-concepts, as well as main effects, were also uncovered. This study helps differentiate LMX from LMXSC and understand the role of self-conceptions, including self-conceptions attributed by employees to the leader, in leader-member relationships.